TrackerSoft - Solución de Facturación de actividades de software - Silva Espinosa, Brian Andrés; Moreno Rosania, Jorge Luis (Universidad Antonio Nariño, 2022)
According to the experience in the pas sage through different software development companies, it has been identified that there is a complexity or process that requires considerable effort by different analysts to perform the billing of software activities, in the different projects that are be ing executed by these companies. This billing of activities takes into account the agreed times against the executed times and thus to calculate the effort really invested by the work teams in the projects, sometimes this process requires different validat ions, from the input given by each member of the team, to the billing of activities that is the basis for an economic billing. This document includes an applied analysis process, since the structured analysis and design model was used to follow up the deve lopment of the information system, which allows the identification of the problem, using observation techniques, understanding and organization of the processes, for the definition of inputs and outputs of the system. It is intended to ensure compliance a nd delivery against the functional and nonfunctional requirements of the system. The development environment in which the project was worked was Java as programming language, the database management engine is ORACLE, coding in the JAVA programming languag pattern of model view controller.